2016
DOI: 10.4172/2165-7548.1000336
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirosis: a Global Health Burden in Review

Abstract: Leptospirosis is a zoonotic disease transmitted by fresh water and mammalian vectors in predominantly tropical regions, with an incidence of 0.1-10 per 100,000 in temperate climates, 10 or more per 100,000 in tropical climates, and up to 100 or more per 100,000 during outbreaks. Its rate of transmission spikes in areas affected by natural disasters such as floods and heavy rainfall and, because it often presents with non-specific symptoms, it can be difficult to diagnose. The case fatality rate in severe lepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
(53 reference statements)
0
6
0
1
Order By: Relevance
“…High-risk groups vary by location and include people that are in contact with livestock, e.g., farmers and meat workers, people in contact with rodents, e.g., sewage workers, rice paddy workers, subsistence farmers and urban slum dwellers, people involved in water-based recreational activities and people affected by extreme weather events, such as flooding [ 4 ]. The burden of disease is often higher in tropical regions with incidence greater than 10/100,000 compared to temperate countries where incidences range between 0.1–10/100,000 [ 11 ]. A systematic review of studies from 1970 to 2008 revealed highest estimates for leptospirosis morbidity and mortality in Oceania, the Caribbean, Southeast Asia, East Sub-Saharan Africa and Andean, Central, and Tropical Latin America [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…High-risk groups vary by location and include people that are in contact with livestock, e.g., farmers and meat workers, people in contact with rodents, e.g., sewage workers, rice paddy workers, subsistence farmers and urban slum dwellers, people involved in water-based recreational activities and people affected by extreme weather events, such as flooding [ 4 ]. The burden of disease is often higher in tropical regions with incidence greater than 10/100,000 compared to temperate countries where incidences range between 0.1–10/100,000 [ 11 ]. A systematic review of studies from 1970 to 2008 revealed highest estimates for leptospirosis morbidity and mortality in Oceania, the Caribbean, Southeast Asia, East Sub-Saharan Africa and Andean, Central, and Tropical Latin America [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it should be highlighted that even now leptospirosis is underdiagnosed in many countries, Vietnam included. Due to significant polymorphism of its clinical course and shortcomings in laboratory diagnostics, leptospirosis is often misdiagnosed as some other febrile illnesses such as dengue, scrub typhus, or chikungunya [30,32,38,65]. In Vietnam, nationwide reporting on infectious diseases is carried out by the General Department of Preventive Medicine of the Ministry of Health.…”
Section: Leptospirosis In Humansmentioning
confidence: 99%
“…For instance, in the protein-based diagnosis of Dengue, the type 1 non-structural protein (NS1) is highly specific and detectable in serum from the first day after fever onset, whereas the sensitivity of specific IgM increases after the first few days 12,21 . For Leptospirosis, despite the low sensitivity, PCR-based methods are more useful for early diagnosis than the gold standard protein-based microscopic agglutination test 35 .…”
Section: Rapid Diagnostic Testsmentioning
confidence: 99%